Understanding the Complexity of the Causes of Student Activism in Higher Education Using the Case of Makerere University - Mukasa, Bart (East African Journal of Education Studies, 2025)
This qualitative study examines the complexities and causes of student activism at Makerere University, Uganda, using Altbach’s theory of student activism as its guiding framework. A qualitative approach to research was used to collect data. The research involved 14 purposively sampled participants. Among these, were eight student leaders and six university administrators, who were interviewed to provide insights into the dynamics of student activism. Thematic analysis revealed key issues driving activism, such as demands for transparency, concerns over tuition increments, inadequate infrastructure, and limited academic freedom. Findings highlight frequent power struggles between student leaders and administrators, often resulting in stalemates that hinder meaningful reforms. The study recommends that student leaders focus on developing leadership and negotiation skills, fostering unity, engaging in constructive dialogue, and prioritizing inclusive representation. Similarly, university administrators are encouraged to establish open communication channels, involve students in decision-making, address their concerns promptly, promote transparency, and support student leadership development. These recommendations aim to foster collaborative engagement and create a harmonious academic environment. By shedding light on the root causes and dynamics of student activism, the study contributes to policy development and strategic approaches for managing activism constructively